Hypoxic-ischemic encephalopathy, intraventricular hemorrhage in the fetus and newborn - Aleksandra N. Balakina; Alina V. Mokh; Albina R. Polishchuk (LLC "MEDIAFORMAT", 2023)
The article presents a clinical observation of a newborn with hypoxic-ischemic encephalopathy and intraventricular hemorrhage.